Phase stress determination and simulation for AZ composite having stress gradient in orthopedic applications - Le, Chi Cuong; Chau , Thi Anh Tuyet (Journal of Technical Education Science, 2016)
The X-ray stress of dual-phase composite AZ is determined from X-ray elastic constants by using Reuss, Voigt and Eshelby–Kroner models. The simulated result showed that the compound XEC in the Reuss model is independent of the volume composition of inclusion Al2O3 and it is valid for low inclusion composition. The Voigt and Eshelby-Kroner models gave closed stress values to the experimental result, while they are constant for the Reuss model.